Morphology and properties of (Ba, Sr, Ca) titanates synthesized by microwave-assisted hydrothermal method - Souza, A. E. [UNESP]; Santos, G. T. A. [UNESP]; Silva, R. A. [UNESP]; Moreira, M. L.; Volante, D. P. [UNESP]; Teixeira, Silvio Rainho [UNESP]; Longo, Elson [UNESP] (IOP Publishing, 2011)
Ba1-xCaxTiO3, Ba1-xSrxTiO3 and Sr1-xCaxTiO3 (x = 0, 0.25, 0.50, 0.75 and 1) nanoparticles were synthesized using the microwave-assisted hydrothermal method. Samples were prepared for 40 minutes at 140°C under a pressure of 3 MPa using an adapted domestic microwave oven. The samples were characterized by X-Ray diffraction (XRD), scanning electron microscopy (FE-SEM), and Raman, photoluminescence (PL) and ultraviolet-visible (UV-Vis) spectroscopies. XRD data show that ceramic powders have crystalline phases associated with a short-range structural disorder. This structural disorder is confirmed by Raman spectral bands indicating multi-phonon processes and the presence of defects or impurities. Such defects account for a broad band in the photoluminescence spectrum in the green light (460 nm) region for all samples. Gap energy variation, obtained from UV-Vis spectra, suggest a non-uniform band structure of these titanates in accordance with the PL results. The morphology of each sample is changed with doping and varies from a spherical to cubic appearance for energy minimization.